The global research status and trends of the application of endoscopic ultrasonography in pancreatic tumors over the last decades: A bibliometric study - Xia, Chuanchao; Yin, Hua; Zhang, Kecheng; Wang, Zhenhuan; Yang, Xiaoli; Huang, Haojie (Frontiers in Oncology, 2022)
Background: To describe the development process and structural relationships of scientific achievements in endoscopic ultrasonography (EUS) in pancreatic tumors over the past decades and to reveal the key research topics using bibliometric analysis. Methods: All relevant publications covering the research of EUS in pancreatic tumors from 1984 to 2021 were involved through the Web of Science Core Collection. R-bibliometrix was used to conduct the bibliometric analysis, and VOSviewer software was used to explore the hot spots and networks related to this field. Results: Between 1984 and 2021, 4071 publications were involved. The number of annual publications increased from 1 to 310. The United States contributed the most publications to this field (n=1433, 35.20%), followed by Japan (n=827, 20.31%) and Germany (n=319, 7.84%). There was active cooperation between countries/regions. Gastrointestinal Endoscopy (GIE) was the most productive journal and the most influential journal. Professor Giovannini M, who produced the most publications, had a great influence on this research. The focus in this field was clarified by analyzing the top 10 citations and co-citations publications. Moreover, the analysis of the keywords showed Important topics: “Classification of pancreatic tumor disease” “Development of EUS in the diagnosis of pancreatic tumor diseases,” and “Development of EUS in the treatment of pancreatic tumor diseases.” Conclusion: For the first time, bibliometric analysis was used to gain a deep understanding of the global trends of studies investigating EUS in pancreatic tumor diseases. The EUS field is rapidly evolving, and our study may be a critical reference for clinical researchers related to this field.